Analisis Saluran Pemasaran Kelapa Sawit Rakyat Di Kelurahan Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis - Sitompul, Dicky Fernando; Saleh, Khairul (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
The Objectives of the research are 1) to find out the marketing channels for smallholder oil palm in Pematang Pudu Village, Mandau District, Bengkalis Regency, 2) To find out the marketing margin and Farmer’s Share of smallholder oil palm marketing channels in Pematang Pudu Village, Mandau District, Bengkalis Regency, 3) To find out how level of efficiency of community coconut marketing channels in Pematang Pudu Village, Mandau District, Bengkalis  Regency. The research method used was observation and direct interviews with respondents using a list of questions (questionnaire). The sampling technique in this research is purposive and snowball sampling where the population of farmers is 191 farmers, the sample was taken using the Sovlin formula, namely 36 farmers, 6 collecting traders, and 1 wholesaler. The research  results show that there are 2 marketing channels, the first channel with a marketing margin of IDR 200/Kg, with a Farmer’s Share of 80%. Then it is said to be efficient because the marketing efficiency results are 8% 50%. Second Marketing Channel with a marketing margin of IDR 200/Kg, with a Farmer’s Share of 90%, then it is said to be efficient because the marketing efficiency results are 10% 50%.